2014
DOI: 10.7763/ijcea.2014.v5.386
|View full text |Cite
|
Sign up to set email alerts
|

Polyindole Based Nickel-Zinc Oxide Nanocomposite – Characterization and Antifungal Studies

Abstract: Abstract-In the present work polyindole based nickel-zinc oxide nanocomposite was prepared. Here nickel-zinc oxide was prepared separately in presence of capping agent using well known co-precipitation method. Polyindole based nickel-zinc oxide nanocomposite was prepared using chemical oxidation method. Polyindole and nickel-zinc oxide was also prepared separately to compare their properties with their counterparts. The samples have been analysed using SEM, FTIR, XRD techniques. Polyindole showed a cauliflower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Our previous work reported that the doping of PIn with perchloric acid (HClO 4 ) could improve its electrical conductivity by many orders of magnitude to support various electronic applications. 34 Recently, PIn was applied as an antifungal material for the fungi Penicillium chrysogenum 35 and as a capacitor, 36 humidity sensor, 37 methanol sensor, 38 etc. Furthermore, PIn-composited graphene based materials can be applied in various electronic applications; for example, GO/PIn composite was utilized as a supercapacitor, 36 GO/PInincorporated Ag was applied as an electrode material, 39 and rGO/PIn nanocomposite was used as a capacitor.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work reported that the doping of PIn with perchloric acid (HClO 4 ) could improve its electrical conductivity by many orders of magnitude to support various electronic applications. 34 Recently, PIn was applied as an antifungal material for the fungi Penicillium chrysogenum 35 and as a capacitor, 36 humidity sensor, 37 methanol sensor, 38 etc. Furthermore, PIn-composited graphene based materials can be applied in various electronic applications; for example, GO/PIn composite was utilized as a supercapacitor, 36 GO/PInincorporated Ag was applied as an electrode material, 39 and rGO/PIn nanocomposite was used as a capacitor.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Devadathan and Raveendran (2014) worked on polyindole-based nickel-zinc oxide nanocomposites to identify the antifungal properties, and they proved that a non-composite could be used as an antifungal material for the fungi Penicillium Chrysogenum (45). However, the use of animal models, as well as various treatment methods and nanoparticles with different concentrations and shapes, presents new horizons for further research to investigate the applications of nanotechnology (46).…”
Section: Discussionmentioning
confidence: 99%
“…This study revealed a higher swelling capacity and controlled delivery of drug by oxidized starch/CuO nanocomposites than pure oxidized starch [148]. Dedhila Devadathan et al compared antifungal activities of their synthesized polyindole based nickel-zinc oxide nanocomposite, nickel-zinc oxide, polyindole, nickel oxide and zinc oxide and observed that polyindole based nickel-zinc oxide nanocomposites showed antifungal activity of 1cm, nickel-zinc oxide showed antifungal activity of 0.7cm and polyindole, nickel oxide and zinc oxide showed no antifungal activity [149]. Faisal Mukhtar et al reported antibacterial properties against E. coli of synthesized binary NiO-Fe 2 O 3 and NiO-CdO nanocomposites and ternary NiO-Fe 2 O 3 -CdO nanocomposite.…”
Section: Biomedical Applicationsmentioning
confidence: 99%